2018
DOI: 10.1108/ijshe-04-2017-0054
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the limits of assessing sustainability at Universidad San Francisco de Quito USFQ, Ecuador, while reporting for a North American system

Abstract: Purpose Universidad San Francisco de Quito, USFQ, completed an assessment study to understand its performance in sustainability in 2012. This study aims to recognize the limitations of applying a North American rating system considering relevant criteria to a South American university and to emphasize the importance and lack of benchmarks available in the region. Design/methodology/approach Methodology used for this study is based on the Sustainability Tracking Assessment Rating System (STARS) by AASHE. In D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Another finding is the lack of assertiveness in transportation and commuting. Despite the efforts to promote cycling or other clean alternatives, it seems to be a trend in countries with Geographical difficulties such as Ecuador and Colombia permeated with the Andes and other mountains that make students and staff use their own vehicle (Velasco et al, 2018).…”
Section: Discussion Of Findings In the Context Of Latin American And ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Another finding is the lack of assertiveness in transportation and commuting. Despite the efforts to promote cycling or other clean alternatives, it seems to be a trend in countries with Geographical difficulties such as Ecuador and Colombia permeated with the Andes and other mountains that make students and staff use their own vehicle (Velasco et al, 2018).…”
Section: Discussion Of Findings In the Context Of Latin American And ...mentioning
confidence: 99%
“…Precisely, the communication of results in sustainability reports, certification and rankings emerged in this research as an opportunity. In the assessment study made by Velasco et al (2018) arose the need for Latin-American universities to have a guideline for benchmarking that offers comparable results or clear instructions. Although the research was in Ecuador, the analysis covered the attempted methodologies reported in the literature for Latin-American countries referencing only three Countries: Brazil, Mexico, Colombia but all failed (Velasco et al, 2018).…”
Section: Discussion Of Findings In the Context Of Latin American And ...mentioning
confidence: 99%
“…From a country perspective, these types of studies have concentrated on, for instance, institutions from Spain (Lozano, 2011;Berzosa et al, 2017;Ferrero-Ferrero et al, 2018;Zorio-Grima et al, 2018;Brusca et al, 2018), Germany and Austria (Lopatta and Jaeschke, 2014), Germany and Australia (Schaffhauser-Linzatti and Ossmann, 2018), Belgium (Ceulemans et al, 2018), Ghana (Hinson et al, 2015), Canada (Fonseca et al, 2011), New Zealand (An et al, 2017), United Kingdom (Townsend and Barrett, 2015;Bullock and Wilder, 2016), Australia (Gamage and Sciulli, 2017), North America (Sepasi et al, 2018), South America (Velasco et al, 2018), Portugal (Madeira et al, 2011), Scotland (de Aguiar and Paterson, 2017) and Lithuania (Katiliute and Daunoriene, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding sustainability in HEIs, one can find numerous examples of efforts that have been reported from several countries, including, for instance: the United States and Canada [13,14], Italy [15], Ecuador [16], Portugal [17], Brazil [18,19], Turkey [20], Jordan [21], and Colombia [22], among others. At the end of the first decade of 2000, Rauch and Newman [23] derived a qualitative/quantitative methodology to define what a sustainable metric target might be and how it can be used to describe the path for universities towards sustainability, using short to long-term time scales.…”
Section: Introductionmentioning
confidence: 99%